A Sense of Place Through Land Art - Amanda Gabriel; Elisabeth von Essen; Beatrice Guardini; Sara Kjellgren; Claire Peterson; Christopher Staundinger (European Journal of Creative Practices in Cities and Landscapes)
This article investigates the potential of land art as a transformative tool for promoting inclusivity and fostering a sense of belonging in public spaces. Drawing on environmental psychology and participatory urban research, the study explores the cognitive and emotional processes involved in place-making and space (re)appropriation. By examining the artist’s perspective on land art interventions, the paper seeks to understand how these creative practices can re-signify and create place meaning, empowering individuals to become active “placemakers.” The research explore the ways in which land art can enhance awareness of place, foster a sense of agency, and contribute to the creation of more inclusive and socially vibrant urban environments. We are inspired by the Land art movement that emerged in the 1960s, specifically inspired by Europeans’ ephemeral interventions in-and-within the landscape, returnable, with natural materials. In order to explore such possibilities, we focus on land art as a possibility to be used in natural public spaces. These reflections come from teachers and students, all authors of this article, deriving from a project of land art as a part of an international distance master course in environmental psychology, repeated for 3 years. We explore how the creative process of doing a land art project with natural materials from a basic experiential perception of the art-processes unfolds within a public space in different parts of the world, exploring aspects that facilitate or impede such potentials of place creation and awareness of place. Reflections on experiences of creating land art projects are presented exploring the basic perception of inner processes connected to place that are cognitive, somatic and embodied, moving towards a deeper relationship with place, touching upon place meaning, identity and attachment. The findings highlight the potential of individual land art experiences as means of engaging with and reimagining public spaces, raising questions about the rights to the city and the public space, and highlighting the awareness that a land art project that is ephemeral and natural has an intrinsic value for its users and how this could be beneficial for the individual experiences and wellbeing.